TAHAP TELAAH LINGKUNGAN STRATEGI INTERNAL DAN EKSTERNAL (LUAS ANALISIS LINGKUNGAN INTERNAL DAN EKSTERNAL) - Mahfud; Hasma B; Mardyawati (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
The external environment plays a crucial role in the sustainability of an institution. The purpose of this study is to analyze and describe the external environment of Islamic educational institutions. This study was conducted without a research location, with all data collected through previous studies in the form of books and scientific articles relevant to the research theme. The data collection technique in this study used documentation, with data analysis techniques including data reduction, data presentation, and conclusion drawing. The results of this study found that the external environment of Islamic educational institutions is an external environment that has the potential to influence the organization. This study also examines weaknesses and threats. Keywords: Environment, External, internal, Islamic educational institutions.